ANALISIS KUALITAS PELAYANAN DI BALAI PELAYANAN PENEMPATAN DAN PERLINDUNGAN TENAGA KERJA INDONESIA (BP3TKI) SEMARANG PROVINSI JAWA TENGAH - Suciningati, Suciningati; Hariani, Dyah; Lestari, Hesti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Hall Placement Services and Protection of Indonesian Workers (BP3TKI) is a public organization that provides services to Indonesia and the Labour Candidate Indonesian Workers in the field of manufacturing services Identity Card Work Abroad (KTKLN). BP3TKI Semarang is an organization built from the National Agency for the Placement and Protection of Indonesian Migrant Workers (BNP2TKI). This study aims to identify and obtain a clear picture of the quality of services provided BP3TKI Semarang and also identify dimensions that lead to a poor quality of service. Type used is descriptive qualitative view of the six terms of quality of service and also the five dimensions of service. The results showed that the quality of services provided and also less than the maximum of five dimensions of service showed a poor value. It is evident from the results of the interview. To improve the quality of care in BP3TKI KTKLN Semarang should consider service user satisfaction.